Monetary Policy Regimes : A DSGE Model Approach - Mašek, František; Potužák, Pavel; Chytilová, Helena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2019)
This thesis investigates different monetary policy regimes within the medium-scale DSGE model. The prolonged decline in the natural rate of interest in developed countries has increased the probability of hitting the zero/effective lower bound (ZLB/ELB) when easing monetary policy. This development raises questions about the suitability of the current inflation targeting regime for today's macroeconomic environment. Frequently discussed alternative regimes, namely price level targeting, nominal GDP growth rate targeting, and nominal GDP level targeting, are compared with the IT regime as well as among themselves within the DSGE model that incorporates various nominal and real rigidities. The regimes are compared both when the central bank does not take into account the ZLB/ELB while setting its policy rate and also when this inequality constraint is included in the model. While the comparison of the regimes is ambitious in the case without the lower bound, the inclusion of the ELB/ZLB shows the positive characteristics of the level targeting regimes compared to the growth rate ones, mainly in response to a negative demand shock. These findings thus rationalize to reassess the suitability of the current inflation targeting regime, provided that there is a considerable probability of more frequent monetary policy conducting at the ZLB/ELB situation in the future.
Vedoucí práce: Pavel Potužák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses